A preservação de documentos eletrônicos de caráter arquivístico: novos desafios, velhos problemas - Katia de Padua Thomaz (2004)
The continuous growth of electronic documents, particularly born-digital documents, has threatened human ability to continue using records as a reliable information source due to the new challenges imposed by the preservation. This evidence and their long term consequences to the nation's history and identity configured the basis of the present thesis. The lack of a consolidated research methodology in the field demanded the development of a specific process. First, the complex nature of theelectronic document archival environment denoted the need to conceive a synthetic digital preservation model in the beginning of the investigation. Second, as it was impossible to directly observe long term digital preservation cases or experiences, the information technology changes which, in some way, can be considered as induced obsolescences, was investigated. Based upon previous premises, the present research adopted a descriptive-qualitative approach, in wich the groundedtheory method was applied through multiple-case studies. The main purpose was to look for factors to be monitored in an electronic document archival environment in order to assure its long term preservation. The data gathering process envolved sixteen information technology changes successfully promoted by four large Brazilian public organizations in the period of 2000-2002, and included techniques such as the content analysis on the records of the changes; individual interviews with the information technology support manager; and focal group interviews with 40 computer specialists who volunteered to participate in this research. The investigation core results include 160 digital preservation conditioning factors, that are impositions resulting from circunstances or previous decisions, which should be observed for the long term digital information preservation; a glossary of digitalpreservation terms and concepts for consultation and use by the archival community and other information professionals; and a digital preservation analytical model developed with the Unified Modeling Language (UML) representation, that demonstrates the interrelationship between major stakeholders of the long term preservation process and serves as a situational reference to understand, analyse and design a digital preservation system in organizations. The conditioning factorswere also analysed facing three fundamental aspects of the literature. Primarily, they were compared to a synthesis of digital preservation problems appointed by the studied authors. Similarly, they were collated with the nine digital preservation requirements identified by Bullock (1999). Finally, the conditioning factors were suited to the six archival functions designed in the Open Archival Information System OAIS reference model (CCSDS, 2002).